Geographic Information System for a Community-Based Water Quality Mapping of Rivers in Indonesia - ‘Uyun, Shofwatul (Universitas Muhammadiyah Malang, 2020)
River Water with good quality status is the primary needs for the Indonesian people who live along the river. Indonesia has more or less 303 rivers with varied status of water quality. On the other side, the government is obliged to conduct the current situation mapping and to spread the status of river water quality to the surrounding society. It is certainly not an easy job considering the amount and width of the monitoring area. Therefore, this research has proposed a new concept to map the status of river water quality using the STORET method by involving the active participation of the local river community. The locations of research are: Kambaniru river, Brantas river, dan Gajah Wong river. There are seven parameters used to determine the status of river water quality those are: temperature, EC/DHL, TDS, PH, DO, BOD and Caliform. The river community can report the data of analysis result into a system in accordance with the sampling location by enclosing the spatial data. The system will present the status of water quality starting from each point of location to the status of water quality of certain river. The testing result functionally indicates that the system is able to give perfect accuration value. While from its usability, the respondents’ responses are as follows: very agree 60.40%, agree 37.95%, and disagree 1.65%.